Agonistic and Epistemic Pluralisms: A New Interpretation of the Dispute between Emilie du Châtelet and Dortous de Mairan. Issue 1 (March 2017) - Rey, Anne-Lise
Abstract : The object of this article is to lay bare the consensualist presuppositions implicit within contemporary analyses of the controversies of the Classical Age by proposing an alternative model: agonistic pluralism. The convergence between this political reading of the controversies and an epistemological reading is reinforced by a discussion of Hasok Chang's work, which develops a model of epistemic pluralism that breaks away from studies in the history of science undertaken following the Kuhnian model of scientific revolutions. This makes it possible to question the theoretical convergence of two anti-hegemonic claims: one political, the other epistemological. I aim to put this new model of analysis to the test by applying it to a well known, oft-analysed dispute, that which erupted between Dortous de Mairan and Emilie du Châtelet following the publication of the Institutions de Physique (Foundations of Physics).